Innovation and practice of professional training based on “One Syndrome and One Product” for clinical nurses (脑病科“一证一品”临床护士业务学习创新与实践) - FU Jingna (付景娜); TIAN Runxi (田润溪); LI Jie (李杰); YANG Junhang (杨俊行); HU Zhe (胡哲); ZHEN Liping (郑莉萍) (中西医结合护理)
A diversified training mode including physician-nurse cooperation ward round based on “One Syndrome and One Product”, “one-to-one ” plan, video-assisted mode is effective to improve the enthusiasm of professional learning of nurses, and comprehensively improve the professional skills and comprehensive abilities of specialized nurses. Based on the “One Syndrome and One Product” project, Innovation and practice of professional training were made to improve the enthusiasm of professional learning of nurses, enhance understanding the nature of the specialized nursing care, improve quality of Traditional Chinese Medicine nursing, provide professional and standardized nursing service, reflect the professional values of nurses, build a service brand with Traditional Chinese Medicine specialized nursing techniques. (“一证一品”医护一体查房模式、“一帮一计划”、视频录制查房模式等多元化新型培训模式能有效地激励和促进护理人员业务学习的积极性, 全方位提升专科护士的综合素养和技能操作水平。科室基于循证理念的“一证一品”项目, 在临床护士业务学习中大胆创新与实践, 充分调动护士学习热情和积极性, 旨在深化专科护理内涵建设, 提升中医护理服务质量, 使患者获得专业化、同质化的护理服务, 从而体现护士的职业价值, 推进中医特色护理服务, 努力形成中医专科护理服务品牌。)